2013
DOI: 10.1371/journal.pone.0080346
|View full text |Cite
|
Sign up to set email alerts
|

High Endemicity and Low Molecular Diversity of Hepatitis B Virus Infections in Pregnant Women in a Rural District of North Cameroon

Abstract: BackgroundA program, supported by the GEMHEP (Groupe d'étude Moléculaire des Hépatites), was established in 2007 in the sanitary district of Tokombéré, to prevent perinatal transmission of hepatitis B virus (HBV). It comprises screening for HBV surface antigen (HBsAg) in all pregnant women and vaccinating the newborn if tests are positive.Methods/Principal Findings1276 women were enrolled in the study after providing informed consent. Demographic data and blood samples were available for 1267 of the enrolled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 41 publications
6
53
5
1
Order By: Relevance
“…These results differed from those obtained by Ducancelle et al in 2013 in the North among pregnant women (20.4%) and those obtained by Foupouapouognigni et al in the East, in 2011, among the Baka and Bakola Pygmies (11.8%). We recorded the lowest prevalence rate in the South Region, followed by the West with 5.22% and 7.72% respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…These results differed from those obtained by Ducancelle et al in 2013 in the North among pregnant women (20.4%) and those obtained by Foupouapouognigni et al in the East, in 2011, among the Baka and Bakola Pygmies (11.8%). We recorded the lowest prevalence rate in the South Region, followed by the West with 5.22% and 7.72% respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…Although HBV is endemic in much of Sub-Saharan Africa (defined as an HBV surface antigen positive test result rate of >8%), and most studies show high rates of positive test results for HBV e antigen [7, 8], a few pediatric studies have suggested that, in Africa, there is a higher HBV acquisition risk after—instead of during—the perinatal period [4,17]. Owing to this gap in the literature, the present study estimated rates of vertical and horizontal transmission on the basis of the available data [4,7], and assumed a broad range of horizontal transmission (5%–30%). However, the results obtained were not sensitive to this wide range.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, almost all of our patients had a serological marker of previous HBV infection. The high prevalence of HBV infection was consistently reported in various groups of patients in Cameroon: 10.1 % in blood donors [12], 20.4 % in pregnant women [10], 23.6 % in health care workers [11] and 33 % in the Bantus enrolled in Central, South, North West and East part of the country [13]. Our findings regarding HBV prevalence in HCC is in keeping with data reported for decades in Gabon (40.5 %) and many studies conducted in West African countries like Niger (73 %), Senegal and Mali (63 %), Gambia (60 %) and Nigeria 61 % [26, 34–36].…”
Section: Discussionmentioning
confidence: 99%